2017
DOI: 10.1098/rsos.171308
|View full text |Cite
|
Sign up to set email alerts
|

The shape of the contact–density function matters when modelling parasite transmission in fluctuating populations

Abstract: Models of disease transmission in a population with changing densities must assume a relation between infectious contacts and density. Typically, a choice is made between a constant (frequency-dependence) and a linear (density-dependence) contact–density function, but it is becoming increasingly clear that intermediate, nonlinear functions are more realistic. It is currently not clear, however, what the exact consequences would be of different contact–density functions in fluctuating populations. By combining … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
40
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(40 citation statements)
references
References 48 publications
0
40
0
Order By: Relevance
“…K = 0.8–0.9 or K = 0.1–0.2; Figure ). Furthermore, a recent modelling study showed that even in cases where nonlinear (sigmoid) and linear transmission functions were so similar that they would be difficult to statistically differentiate, the functions had distinct impacts on the probabilities of pathogen invasion and persistence (Borremans, Reijniers, Hens, et al, ). Therefore, infectious disease modelling would benefit more careful and creative study designs that tease apart underlying transmission mechanisms and their relationships to host density, and from innovation in statistical or other methodological tools that improve our abilities to confidently compare and choose transmission functions, like our new contactr r package.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…K = 0.8–0.9 or K = 0.1–0.2; Figure ). Furthermore, a recent modelling study showed that even in cases where nonlinear (sigmoid) and linear transmission functions were so similar that they would be difficult to statistically differentiate, the functions had distinct impacts on the probabilities of pathogen invasion and persistence (Borremans, Reijniers, Hens, et al, ). Therefore, infectious disease modelling would benefit more careful and creative study designs that tease apart underlying transmission mechanisms and their relationships to host density, and from innovation in statistical or other methodological tools that improve our abilities to confidently compare and choose transmission functions, like our new contactr r package.…”
Section: Discussionmentioning
confidence: 99%
“…The more that density varies, the more that choosing the correct transmission function matters (Borremans, Reijniers, Hens, & Leirs, ). This choice is often simplified into a dichotomy between the two linear, canonical transmission functions: density‐dependent transmission (hereafter DD transmission) and density‐independent or frequency‐dependent transmission (hereafter FD transmission; Figure ; also see Appendix ).…”
Section: Introductionmentioning
confidence: 99%
“…Mastomys natalensis has a promiscuous mating system and is not territorial or aggressive towards conspecifics (Kennis, Sluydts, Leirs, & Hooft, ). Home range overlap is generally high and increases significantly with abundance, suggesting contact rates to be density‐dependent, probably nonlinearly (Borremans et al, , , ). Given that MORV transmission is most likely density‐dependent, infection is predominantly acute, and the immune response is lifelong, it is surprising that MORV can persist during low host density periods, when host density would be expected to be below the N T (Goyens, Reijniers, Borremans, & Leirs, ).…”
Section: Methodsmentioning
confidence: 99%
“…Given the difference in persistence probability, understanding the role of these different parasite-host characteristics is an important prerequisite for the development of wildlife disease control programs (e.g. to predict the effectiveness of culling to eliminate a disease; Morters et al, 2012;Borremans, Reijniers, Hens, & Leirs, 2017 in natural conditions, we performed a small laboratory experiment in which wild-caught rodents were caged and sampled for 8 weeks.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to assumptions about the likely values of a few poorly understood model parameters, our approach relies on a relatively simple mathematical model that simplifies population age structure, assumes density dependent infection and spatially homogenous transmission rates. Relaxing these assumptions could, in principle, alter our quantitative estimates for some model parameters (Borremans et al 2017). Finally, our estimates of parameters are based on data collected over 14 years ago, creating the possibility that ecological, sociological, or evolutionary change in Lassa virus, the reservoir M. natalensis , or human populations with which the reservoir is commensal have caused values of important parameters to change.…”
Section: Discussionmentioning
confidence: 99%